Effect of Moringa oleifera seed extract on antioxidant activity and sperm characteristics in cryopreserved ram semen - Carrera Chavez, Jose Maria (2020)
Semen cryopreservation damages sperm due to oxidative stress. This study evaluated the antioxidant capacity of Moringa oleifera seed extract in cryopreserved ram semen and the impact of the extract on sperm characteristics. Semen from eight hair rams (four rams per sampling) was allocated into four groups, according to their treatment prior to cryopreservation: Control (no extract), 0.5 (M0.5), 5.0 (M5.0), and 10.0 (M10) mg/mL of M. oleifera extract. The antioxidant activity (ferric reducing antioxidant power, FRAP) and the spermatic characteristics (sperm viability; progressive motility; fast motility; slow motility; acrosome damage; membrane damage; and mitochondrial activity) were assessed post-thawing. Variables were evaluated with analysis of variance followed by Tukey test. While no significant differences were detected in acrosomal damage, mitochondrial activity, fast-, or slow motility, the antioxidant activity was higher (P < 0.05) in M0.5 and M5 treatments. Viability and progressive motility increased in the M0.5 group (P < 0.05), whereas sperm membrane damage was lower (P < 0.05) in the same treatment. In conclusion, supplementation of ram semen with M. oleifera seed extract enhances antioxidant activity, sperm membrane integrity, viability, and progressive motility after thawing. This suggests that M. oleifera extract could be used as an antioxidant to improve the outcome of semen cryopreservation.